Pelaksanaan Aqiqah Ditinjau Dari Fiqih Syafi’iyah - Desi Maladewi Hrp & Muhammad Arsad Nasution (Jurnal El-Thawalib, 2021)
This research is based on the implementation of aqiqah in Wek IV Sub-District, North Padangsidimpuan District, Padangsidimpuan City, which performs aqiqah on adult children and is carried out the day before the child is married. The formulation of the problem in this study is how the implementation of aqiqah in Wek IV Village and how the implementation of Aqiqah in Wek IV Village is viewed from Islamic law according to Fiqih Syafi'iyah, as well as what causes people to implement aqiqah after adult children. The purpose of this study was to determine the implementation of aqiqah in Wek IV Village, to find out the review of Islamic law according to the Syafi'iyah School of Religion on the implementation of aqiqah after adulthood, and to find out why the Wek IV community carried out aqiqah as an adult. This research uses qualitative research. The results of this study indicate that the implementation of aqiqah in Wek IV Village globally has fulfilled the aqiqah. It can be seen in its implementation the community has slaughtered the aqiqah animal that had been determined by the Syafi'iyah fiqih. However, when viewed from a harmonious perspective, it is not in accordance with the provisions of Fiqih Syafi'iyah because the child who is diaqiqah is already baligh and does not cut the hair of the child he qiqah. As for the background of the Wek IV community in carrying out aqiqah on adult children because it has become a custom that is passed from generation to generation to carry out aqiqah when the child is an adult.